National Current Care Guidelines for paediatric lower respiratory tract infections reduced the use of chest radiographs but local variations were observed. (7th December 2020) - Poutanen, Roope; Virta, Tuija; Heikkilä, Paula; Pauniaho, Satu‐Liisa; Csonka, Peter; Korppi, Matti; Renko, Marjo; Palmu, Sauli
Abstract: Aim: Our aim was to evaluate the impact of the 2014 Finnish Current Care Guidelines for paediatric lower respiratory tract infections (LRTIs), particularly on taking of chest radiographs. Methods: This study used official national data and regional (Pirkanmaa) data on children aged 0‐16 years who underwent chest radiographs in 2011 and 2015. We also collected data for LRTI diagnoses from local registers, including prescribed antibiotics and taking of chest radiographs. The local cohort comprised children aged 0‐15 who presented to the primary care emergency room or to the hospital emergency department (Tampere university hospital) in November‐December 2012‐2015. Results: Chest radiographs for Finnish children aged 0‐16 fell from 2011 to 2015: by 15.9% nationally and by 16.9% in Pirkanmaa. When asylum seekers with chest radiographs for tuberculosis screening were excluded, the estimated national reduction was 29.9%. In the local cohort, chest radiographs increased from 82 to 139 (69.5%) between 2012/2013 and 2014/2015 as the occurrence of community‐acquired pneumonia (CAP) increased. However, the proportion of patients with CAP who had chest radiograph taken tended to decrease from 84.6% to 71.3% ( p  = 0.078). Conclusion: Decreases in national and regional chest imaging trends were observed after the 2014 guidance for children`s LRTI was introduced.